Revision and molecular phylogeny of the spider genus Micaria Westring, 1851 (Araneae: Gnaphosidae) in the Afrotropical Region - Booysen, Ruan; Haddad, Charles R. (Zootaxa, 2021)
The genus Micaria Westring, 1851 (Araneae, Gnaphosidae) is a group of small (1.85–5 mm) ant-like spiders that can be distinguished from other gnaphosids by their piriform gland spigots that are similar in size to the major ampullate gland spigots. According to the World Spider Catalog, there are 105 species of Micaria in the world, of which only three species are known from the African part of the Afrotropical Region, namely M. chrysis (Simon, 1910), M. tersissima Simon, 1910 and M. beaufortia (Tucker, 1923). The objectives of this study were to revise Micaria in the Afrotropical Region, providing new and updated records for each of the species, evaluating the relationships between them using COI barcoding data, and providing information on their biology, mimetic relationships and feeding ecology. These objectives were met by collecting fresh material from the KwaZulu-Natal, Western Cape, Northern Cape and Free State provinces in South Africa. Fresh material of M. tersissima and M. chrysis were collected from their type localities, Komaggas and Port Nolloth (Northern Cape Province), respectively, for identification and DNA analyses. COI sequences generated, together with those sourced from Barcode of Life Data Systems (BOLD) and GenBank, were aligned using the CulstalW alignment algorithm in the Mega X software, and molecular phylogenetic analyses were performed using MrBayes for Bayesian Inference (BI) and RaxML for maximum likelihood (ML) analyses. Morphological examination of the collected and voucher material yielded 17 new species for the Afrotropical Region, namely M. basaliducta sp. nov. (♀, ♂, South Africa), M. bimaculata sp. nov. (♀, ♂, Mauritania), M. bispicula sp. nov. (♀, ♂, Namibia, South Africa), M. durbana sp. nov. (♀, ♂, South Africa, Zambia), M. felix sp. nov. (♀, ♂, Cameroon, Ethiopia, Malawi, Mozambique, Namibia, South Africa, Zambia, Zimbabwe), M. gagnoa sp. nov. (♀, ♂, Côte d’Ivoire, Mozambique, Mozambique, Tanzania), M. koingnaas sp. nov. (♂, South Africa), M. lata sp. nov. (♂, Namibia, South Africa), M. laxa sp. nov. (♀, South Africa), M. mediospina sp. nov. (♂, South Africa), M. parvotibialis sp. nov. (♀, ♂, Senegal), M. plana sp. nov. (♀, ♂, Ethiopia), M. quadrata sp. nov. (♀, Ethiopia), M. quinquemaculosa sp. nov. (♀, ♂, Namibia, South Africa), M. rivonosy sp. nov. (♀, ♂, Madagascar), M. sanipass sp. nov. (♂, South Africa) and M. scutellata sp. nov. (♂, South Africa). Furthermore, both sexes of M. beaufortia, as well as the male of M. tersissima, are redescribed. Both sexes of M. chrysis are described for the first time, as this species was only known from a juvenile. Of the previously known species, M. beaufortia (Botswana, Ethiopia, Lesotho, Namibia, South Africa, Zimbabwe) and M. chrysis (Côte d’Ivoire, Ethiopia, Lesotho, Namibia, South Africa, Tanzania) are widespread in the Afroptropics, while M. tersissima is only known from South Africa. Both the Bayesian inference and the maximum likelihood analysess recovered Micaria (sensu lato) as monophyletic with the inclusion of the subopaca group. The pulicaria species group was recovered as polyphyletic in both the BI and ML analyses. Four Afrotropical species, as well as the M. rossica Thorell, 1875/M. foxi Gertsch, 1933 group, formed a clade sister to M. formicaria (Sundevall, 1831). Eight of the Afrotropical species now have COI barcoding data uploaded to BOLD.